Early Stages of Bacterial Colonization Development After Xanthomonas campestris Seed Inoculation in Selected Brassica Species - Vojtěch Ferby; Lucia Nedorost Ragasová; Jakub Pečenka; Agnieszka Sękara; Robert Pokluda (Horticulturae)
This study investigates Xanthomonas campestris pv. campestris (Xcc) incidence rates in cabbage, kale, and kohlrabi, focusing on the roots and stems over a 15-day period after sowing. Seeds were inoculated with Xcc, and infection levels were monitored using confocal microscopy combined with fluorescence in situ hybridization. Significant differences in incidence rates were observed across the 15 days using a scale from 0 to 5 (0–100% incidence). Kale exhibited the highest mean incidence rates in roots (3.64), while cabbage and kohlrabi showed greater variability (3.4–3.44). Stem infections were more severe, with kale showing the highest mean levels (4.16), followed by kohlrabi (4.0), and cabbage (3.68). In cabbage roots, incidence rates increased until day 11, after which a significant decline was noted, whereas stem Xcc incidence rates remained stable. Kale roots peaked on day 9, with significant fluctuations on days 13 and 15. Kohlrabi displayed moderate, stable root incidence rates over the 15-day period. In stems, kohlrabi showed a significant increase on day 11, followed by a drop on day 15. Regression analysis revealed a significant positive linear correlation between incidence rate and days of observation in kohlrabi roots. However, no significant trends were observed in stem infections across all species, where incidence rates were high and stable from day 7 onwards. Newly acquired data indicate that the incidence rate of Xcc development depends on the type of vegetable. However, the bacterial occurrence in the root parts does not always correspond with the intensity of Xcc colonization in the stem section of the plants. Even at lower levels of Xcc occurrence in the roots, damage to the vascular bundles can be fatal. These findings offer valuable insights into Xcc infection dynamics, contributing to improved disease management strategies for Brassica crops.